A replacement name for Nemophora divina Diakonoff, 1951 (Lepidoptera: Adelidae), a secondary junior homonym of Nemophora divina (Caradja, 1939) - Kozlov, Mikhail V. (Zootaxa, 2023)
Caradja (1939) described a fairy moth (Lepidoptera: Adelidae) species, Nemotois divina, from Ho Shan, Shanxi province of China. The genus Nemotois Hübner [1825] is a junior subjective synonym of the genus Nemophora Hoffmannsegg, 1798 (Fletcher 1929; Janse 1945; Jacobs 1949; Diakonoff 1951; Powell 1969; Nielsen 1980), and the combination Nemophora divina (Caradja, 1939) was first proposed by Kozlov (1997). This action made Nemophora divina Diakonoff, 1951, described from Indonesia, a secondary junior homonym of Nemophora divina (Caradja, 1939). No synonyms are known for this junior homonym; therefore, a new replacement name is proposed according to ICZN (1999: Art. 60.3). This name is based on the same holotype as the replaced name (ICZN 1999: Art. 72.7).